The lichens and lichenicolous fungi of National Nature Park “Oleshkivs`ki pisky” (Kherson region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The data about 52 species of lichens and 9 species of lichenicolous fungi of National Nature Park “Oleschkivs`ki pisky” are given. 51 from them are new for this territory. Lichenicolous fungus Homostegia piggotii Berk. et Broome – is a new species for plain part of Ukraine. The species are arranged on the reserve areas “Burkuty” (54 species) and “Radenske” (36 species), as well as ecology with substrate characters.
Keywords: locations, Homostegia, Dacampia, Taeniolella, Radenske, Burkuty.